A pretest-posttest pilot study for the development and preliminary validation of a tool for the clinical assessment of radioiodine induced sialadenitis - Christou, Andri; Papastavrou, Evridiki; Merkouris, Anastasios; Charalambous, Andreas (My University, 2021)
The clinical assessment of radioiodine-induced sialadenitis is relied on the observer-defined toxicity grading model. However, this model has significant limitations, the major one being the lack of systematic assessment based on objective criteria. The main aim of this study was the development and testing of an assessment tool which could examine the severity of post-irradiation sialadenitis.
Keywords: Thyroid cancer; Radioiodine therapy; Salivary gland dysfunction; Sialadenitis; Sialadenitis assessment